PRAKTIK PENGALAMAN LAPANGAN TERPADU DALAM PENINGKATAN KUALITAS CALON GURU - Sugeng Mardiyono (LPMPP Universitas Negeri Yogyakarta, 2006)
AbstractConsidering on the Indoesian Teacher and Lecturer Act, every Indonesian teacher needs to have a teacher certification. Indeed, it is a good opportunitiy as well as a challence for every university, which is conducting teacher training program, to have qualified graduates. As a qualified teacher, he must have four competencies concerning pedagogy, attitude, personal, and social. The question that may arise is How to have such competencies? Of course, many ways can be done. However, improving the quality of teaching practicum is one of the many possibilities that can be considered. Integrated Student Community Service - Teaching Practicum (KKN-PPL) which is combiningcommunity service program and teaching practicum itself has been developed by Yogyakarta State University (UNY) to have a better model of such teaching practicum.Being a new model, KKN-PPL must be analized regularly and continuously to get a better quality of it. Infact, it has been evaluated anually by involving some principals or headmasters, students, lecturers,and the developer team of KKN-PPL. There are many comments, suggestions, criticism, and questions of them that need to be responded. However, the three points such as the main reason for having KKN-PPL, the long time periode needed, and the way how to develop it are really good points that need to be clarified. This paper is presented for giving information and answering such questions.Key words: KKN-PPL, Teaching Practicum, Students Teacher